The Absurdity of The Law In The Enforcement of Criminal Acts Fisheries (Illegal Fishing) in Indonesia - Muhammad Fauzi Ramadhan; Airlangga Putera; Miftahul Jannah (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2024)
This research explores legal absurdities in Indonesian law enforcement for illegal fishing, focusing on the forms of absurdity and their impact. The author uses normative legal research to determine that the current legal absurdity in Indonesian law enforcement is due to the ratification of Law no. 11 of 2020 concerning Job Creation in the Maritime and Fisheries Sector, which disharmonizes norms with previous fisheries laws and regulations. This legal absurdity is evident in the unclear phrase "small fishermen," which creates confusion for law enforcement officials and causes unrest in small fishing communities regarding ship administration. The author suggests that the government should prioritize public interests over certain parties' interests in legislation and explore moral values in environmental management, particularly in the maritime sector, to prevent legal absurdities in law enforcement for illegal fishing crimes in Indonesia. Keywords: Legal Absurdit; Law Enforcement; Illegal Fishing